The Roles of First Language and Proficiency in L2 Processing of Spanish Clitics: Global Effects. Issue 2 (26th April 2014) - Seibert Hanson, Aroline E.; Carlson, Matthew T.
<x xml:space="preserve">Abstract</x> We assessed the roles of first language (L1) and second language (L2) proficiency in the processing of preverbal clitics in L2 Spanish by considering the predictions of four processing theories—the Input Processing Theory, the Unified Competition Model, the Amalgamation Model, and the Associative‐Cognitive CREED. We compared the performance of L1 English (typologically different from Spanish) to L1 Romanian (typologically similar to Spanish) speakers from various L2 Spanish proficiency levels on an auditory sentence‐processing task. We found main effects of proficiency, condition, and L1 and an interaction between proficiency and condition. Although we did not find an interaction between L1 and condition, the L1 Romanians showed an overall advantage that may be attributable to structure‐specific experience in the L1, raising new questions about how crosslinguistic differences influence the processing strategies learners apply to their L2.